Enterprise Architecture Planning at DINKOPUKM Salatiga City using TOGAF ADM - Raras, Galuh Hanggana; Bangkalang, Dwi Hosanna (Sistemasi: Jurnal Sistem Informasi, 2024)
In the effort to digitize Micro, Small, and Medium Enterprises (MSMEs) at DINKOPUKM Salatiga, several issues have been identified. These include recurring disruptions to wifi during operational activities, computers with low device specifications, inadequate computer resources, and poorly organized annual reports. Therefore, there is a need for IS/IT alignment to support business processes, such as Enterprise Architecture planning, ensuring that the agency has a standardized IS/IT environment as the strategic foundation for the business processes of DINKOPUKM Salatiga. The planning method used is TOGAF ADM, with the goal of producing a technology development blueprint for DINKOPUKM Salatiga. This blueprint can serve as a recommendation for the development of existing systems and provide a strategy for handling risks in case of technological issues. The benefits of this research include serving as a foundation for system development, evaluating the use of technology, and gaining knowledge in managing potential risks in hardware and software maintenance. The analysis results in the creation of new, more modern business processes, an architectural plan, and the alignment of IS/IT needed for future planning. Additionally, risk identification based on 2 risk factors and 11 risk items produces solutions that can be recommended for addressing emerging issues.